INTERRELATION OF THE ECOLOGICAL LEXICON WITH THE SUSTAINABILITY OF REGIONAL LANGUAGES - Mariam Ulfa; Muhammad Safdar Bhatti (Universitas Muhammadiyah Makassar, 2024)
This research focuses on exploring that the existence of language can be measured from the continuity of the lexicon as the smallest element of language. The use of the ecological lexicon in society is interrelated with the existence of its referent. Based on this, this research uses interdisciplinary studies, namely ecology and linguistics. This research attempts to measure the vitality of the lexicon by recording the ecological lexicon of flora and fauna through lexicon classification. This research aims to find the interrelation between the existence of an ecological lexicon and the survival of regional languages. This research approach uses a qualitative design with the concept of ecolinguistic theory. Data collection techniques in this research used documentation techniques, interviews and literacy studies. The subject of this research uses a sample of regional languages in Indonesia, namely Madurese and the primary subject is linguistic conditions in Pakistan using literacy and documentation studies. The analysis technique for this research uses qualitative descriptive techniques with a referential equivalent method. The results of this research include, among other things, an interrelation was found between ecological conditions and language survival. The active flora ecological lexicon in Madurese is 56% and the active fauna lexicon is 64%. These results are then relevant to the condition and status of the Pakistani language which is facing the threat of extinction in several types of language due to the condition of biodiversity which is starting to become endangered, thus affecting the lexicon referent.